폐리튬인산철 양극재로부터 리튬의 선침출 및 인과 철의 개별적 분리 회수 연구 - 김희선(Hee-Seon Kim); 김보람(Boram Kim); 김대원(Dae-Weon Kim) (Clean Technology, 30(1), 2024)
As demand for electric vehicles increases, the market for lithium-ion batteries is also rapidly increasing. The battery life of lithium-ion batteries is limited, so waste lithium-ion batteries are inevitably generated. Accordingly, lithium was selectively preleached from waste lithium iron phosphate (LiFePO4, hereafter referred to as the LFP) cathode material powder among lithium ion batteries, and iron phosphate (FePO4) powder was recovered. The recovered iron phosphate powder was mixed with alkaline sodium carbonate (Na2CO3) powder and heat treated to confirm its crystalline phase. The heat treatment temperature was set as a variable, and then the leaching rate and powder characteristics of each ingredient were compared after water leaching using Di-water. In this study, lithium showed a leaching rate of approximately 100%, and in the case of powder heat-treated at 800 ℃, phosphorus was leached by approximately 99%, and the leaching residue was confirmed to be a single crystal phase of Fe2O3. Therefore, in this study, lithium, phosphorus, and iron components were individually separated and recovered from waste LFP powder. 전기차의 수요가 증가함에 따라 리튬이온전지의 시장 또한 급증하고 있다. 리튬이온전지의 배터리 수명은 제한되어 있으며, 수명을 다한 배터리의 교체 필연적이므로 폐리튬이온전지 배터리가 발생하게 된다. 이에 리튬이온전지 중 폐리튬인산철(LiFePO4, 이하 LFP라고 함) 양극재 분말에서부터 리튬은 선택적으로 선침출하고 인산철(FePO4) 분말을 회수하였다. 회수된 인산철 분말은 탄산나트륨(Na2CO3) 분말과 혼합하여 열처리하여 그 결정상을 확인하였다. 열처리 온도를 변수로 하였고, 이후 증류수를 이용하여 수침출 후 각 성분의 침출률 및 분말 특성을 비교하였다. 본 연구에서 리튬은 약 100% 침출률을 보였고 800 ℃에서 열처리한 분말의 경우 인이 약 99% 침출되었으며, 침출 잔사는 Fe2O3 단일 결정상으로 확인되었다. 따라서 본 연구에서는 폐LFP 분말로부터 리튬, 인 그리고 철 성분을 개별적으로 분리 및 회수할 수 있었다.